2018
DOI: 10.1177/2045894018764629
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction in pulmonary arterial hypertension: loss of cilia length regulation upon cytokine stimulation

Abstract: Pulmonary arterial hypertension (PAH) is a syndrome characterized by progressive lung vascular remodelling, endothelial cell (EC) dysfunction, and excessive inflammation. The primary cilium is a sensory antenna that integrates signalling and fine tunes EC responses to various stimuli. Yet, cilia function in the context of deregulated immunity in PAH remains obscure. We hypothesized that cilia function is impaired in ECs from patients with PAH due to their inflammatory status and tested whether cilia length cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 41 publications
2
28
0
1
Order By: Relevance
“…Besides BMPR2 mutations, insults such as inflammation, chronic hypoxia, and shear stress have been found to be involved in the pathogenesis of PAH. We demonstrated that the pro‐inflammatory cytokines TNF‐α and IL‐1β, previously found to be implicated in PAH , trigger autophagy in PAECs. Hurst et al reported that TNF‐α reduces BMPR2 transcription in PAECs .…”
Section: Discussionmentioning
confidence: 65%
“…Besides BMPR2 mutations, insults such as inflammation, chronic hypoxia, and shear stress have been found to be involved in the pathogenesis of PAH. We demonstrated that the pro‐inflammatory cytokines TNF‐α and IL‐1β, previously found to be implicated in PAH , trigger autophagy in PAECs. Hurst et al reported that TNF‐α reduces BMPR2 transcription in PAECs .…”
Section: Discussionmentioning
confidence: 65%
“…Increased human serum IL6 protein levels are found across the systemic and lung circulation of PAH patients with mild-to-severe disease and are correlated with clinical phenotypes and outcomes in PAH subgroups [ 34 , 35 ]. Additionally, we have shown that pro- and anti-inflammatory cytokine responses in MVECs of PAH patients are impaired [ 36 ]. In this study, however, we demonstrate that BMP9 or IL6 alone are not sufficient to induce full mesenchymal trans-differentiation, as previously suggested [ 37 39 ], wherefore we postulate that IL6 plays a mechanistic respectively modulating role.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cell responses to FSS through PC help maintain barrier function, blood vessel wall permeability, and vascular tone (Jones et al, 2012;Peng et al, 2019). PC are also involved in endothelial cell inflammatory signaling, as their loss promotes vascular inflammation (Dinsmore and Reiter, 2016), and their length is controlled by cytokine stimuli, as mentioned above (Dummer et al, 2018). Defects in endothelial PC cause disorders of blood fluid-induced responses and result in vascular dysfunctions, such as hypertension, aneurysm, and atherosclerosis (Pala et al, 2018).…”
Section: Endothelial Cellsmentioning
confidence: 99%